Morphological decomposition compensates for imperfections in phonological decoding. Neural evidence from typical and dyslexic readers of an opaque orthography. (September 2020) - Bitan, Tali; Weiss, Yael; Katzir, Tami; Truzman, Tammar
Abstract: The current study examined the widely held, but un-tested, assumption that morphological decomposition can compensate for missing phonological information in reading opaque orthographies. In addition, we tested whether morphological decomposition can compensate for the phonological decoding deficits in readers with dyslexia. Hebrew provides a unique opportunity to test these questions as it has a rich Semitic morphology, and two versions of script: a transparent orthography (with diacritic marks, 'pointed') and an opaque orthography (without diacritic marks, 'un-pointed'). In two experiments, one behavioral and one fMRI, skilled and dyslexic readers read aloud Hebrew nouns: half bi-morphemic (root + pattern) and half mono-morphemic (non-decomposable). Each word was presented both in the transparent orthography (pointed), and in the opaque orthography (un-pointed). While skilled readers were faster, and showed no effects of diacritics or morphology, dyslexic readers read pointed words more slowly than un-pointed words and bi-morphemic words faster than mono-morphemic words. The imaging results showed: 1) In both groups a morphological effect was found in un-pointed words, in left inferior and middle frontal gyri, associated with morpho-phonological decomposition. 2) Only readers with dyslexia showed a morphological effect in pointed words in the left occipito-temporal cortex, associated with orthographic processing. 3) Dyslexic readers also showed a positive association between morphological awareness and activation in the left occipito-temporal cortex during reading of all words, and activation in inferior frontal cortex during reading of un-pointed bi-morphemic words. Altogether, these findings suggest that in both typical and dyslexic readers morphological decomposition can compensate for the missing phonological information in an opaque orthography. The results also show that readers with dyslexia can rely on morphological decomposition to compensate for their deficits in phonological decoding. Finally, these results highlight the way in which unique language specific properties shape the neural mechanisms underlying typical and atypical reading.